IMPLEMENTASI PROFILE MATCHING PADA PRIORITAS APPROVAL PENGAJUAN LAYANAN PREMIUM PADA PT. PLN (PERSERO) ULP SEMARANG BARAT - Setiawan, Aries; Ratnawati, Juli; Prihandono, Adi; Farida, Ida (Jurnal Transformatika, 2022)
Premium services are useful for overcoming blackout problems that often occur in previous regular services, with this service customers will get energy services with very adequate supplies. The system for submitting regular service upgrades to premium services at PLN. ULP Semarang Barat so far has not been able to provide the appropriate decision regarding the customer to be approved for the right type of premium service (bronze, silver, gold and platinum). The level of accuracy resulting from testing 15 data on the old system assessment is 0.87%, this means that profile matching can be referenced as an assessment of granting approval for premium service submissions